Underwater paleontology inside cenotes reveals the Miocene-Pliocene fish diversity in the Yucatan Peninsula, southeast Mexico - Kleyton M. Cantalice; Hugo E. Salgado-Garrido; Erick Sosa-Rodríguez; Kay Vilchis-Zapata; Gerardo González-Barba (PLoS ONE, 2025)
The Yucatan Peninsula, southeast México, hosts a unique underwater karstic system of galleries connected by multiple sinkholes, locally called cenotes. This system is developed on a great Late Miocene to Early Pliocene carbonate platform belonging to the Carrillo Puerto Formation. The karstification process partially erodes these deposits’ surfaces and exposes the fossil assemblage. Here, we present the fossil fish diversity in underwater prospections in the Cenotes Sambulá, San Juan, and X-Nabuy. Our results indicate the presence of at least 11 different taxa, which include: 1) species that live today on Mexican coasts, such as Carcharhinus brachyurus, C. leucas, C. perezii, Carcharodon carcharias, and unidentified Rhinoptera species; 2) extinct taxa, such as †Galeocerdo mayumbensis, †Hemipristis serra, and †Otodus (Carcharocles) megalodon; 3) taxa that are not currently distributed in Mexican coasts, such as Carcharhinus macloti and representatives of the genus Aetomylaeus. Furthermore, a new Diodontidae species, †Chilomycterus dzonotensis sp. nov., is described. It represents an increment in the Neogene fish diversity in the Gulf of Mexico and supports a shallow marine environment associated with a coral reef system. The small size of some teeth indicates that the deposits of Carrillo Puerto could be a shelter for tiny marine organisms, and the presence of some taxa highlights local extinctions in the Western Atlantic during the Late Cenozoic.